Total iron content in dust samples of southernmost Patagonia - Cosentino, Nicolás; Ruiz-Etcheverry, Laura; Bia, Gonzalo; Simonella, Lucio; Coppo, Renata; Torre, Gabriela; Saraceno, Martín; Tur, Verónica; Gaiero, Diego (IEDA: EarthChem Library, 2020)
Abstract: Total iron content of bulk dust (i.e., mineral aerosols) samples of southernmost Patagonia (53.79ºS, 67.75ºW). The purpose of this dataset is to analyze the impact of dust deposition on South Atlantic Ocean biogeochemistry. Other Description: Cosentino NJ, Ruiz-Etcheverry LA, Bia GL, Simonella LE, Coppo R, Torre G, Saraceno M, Tur VM and Gaiero DM (in revision) Does satellite chlorophyll-a respond to southernmost Patagonian dust? A multi-year, event-based approach. Journal of Geophysical Reseach: Biogeosciences.